Effects of Fulvic and Humic Acids on Arsenate Adsorption to Goethite: Experiments and Modeling - Weng, Liping; Van Riemsdijk, Willem H; Hiemstra, Tjisse (Environmental science & technology, 2009)
Data for interactions between arsenate (AsO4 3−) and fulvic acids (FA) or humic acids (HA) at the surface of goethite are presented (pH 3−7, ionic strength 2 mM and 10 mM). Adsorption of FA and HA leads to desorption of arsenate and a correspondingly strong increase of arsenic concentration in solution. Adsorption of both FA and HA is mutually decreased by the competition with arsenate. The competition between FA and arsenate is much stronger than that between HA and arsenate. Using an advanced model, the LCD model (Ligand and Charge Distribution), arsenate adsorption to goethite in the presence of both adsorbed FA and HA can be predicted reasonably well. The stronger effects of FA on arsenate adsorption are caused, according to the model, by its spatial location which is closer to the oxide surface, and as a consequence, the electrostatic interactions between adsorbed FA particles and arsenate ions are much stronger than those for HA particles. The results show that site and electrostatic competition are the major mechanisms explaining the effects of natural organic matter on the arsenic speciation, whereas other possible mechanisms, such as a chemical reduction of arsenate to arsenite and formation of ternary organic arsenic complexes, are of minor significance.